Museum Education and Archaeological Ethics: An Approach to the Illicit Trade of Antiquities. Issue 1 (13th February 2014) - Argyropoulos, Vasilike; Aloupi-Siotis, Eleni; Polikreti, Kyriaki; Apostolides, Rea; El Saddik, Wafaa; Gottschalk, Raymund; Abd el Nazeer, Mona; Vryonidou-Yiangou, Marina; Ashdjian, Peter; Yannoulatou, Maria-Christina; Simon, Stefan; Davis, Wolfgang; et al.
Many museum educational programs and exhibitions worldwide, designed to communicate to the public the importance of archaeology, adopt a treasure hunt approach often inspired by emblematic mass culture figures, such as Indiana Jones or Lara Croft. Alternatively they organize exhibitions on the identification of fakes in the spirit of TV series such as X-files or CSI . These programs usually avoid dealing with a fundamental issue in archaeological practice, which pertains to the paramount importance of context and the scientific consequences of its destruction through, among others, the illicit trade of antiquities. The hesitation in promoting this sensitive topic may be due to the fact that many objects in major museum collections are often unprovenanced. Although the ICOM Code of Ethics for Museums (2006, section 4.5) advises against displaying material of questionable origin, most museums do host such antiquities. The paper explores how museums can begin to discuss the issue of context using the materials produced by the European Culture project Witness the Past (WTP): film documentaries or educational kits and related activities aimed at children on the topic of the importance of context and the destructive effects of the illicit trade of antiquities. The WTP project was implemented in three European museums as well as in Egypt and Jordan.